Towards a Financial-based View of Business Failure - IDRISSI, Khadir; TAOUAB, Omar (Revue Internationale des Sciences de Gestion, 2020)
The survival of a company finds its limit in the problems faced throughout its existence and which are likely to lead her to failure. Indeed, the company can be affected during its existence by several parameters that can compromise its durability, among which we mention: continuous or discontinuous decrease of activity, loss of business orders, debt recovery problems, imbalanced financial structure or a small capitalization, governmental tax adjustment, shareholders changes, key man death, social movement, etc. This makes business failure a transversal, dynamic and complex concept including many sides and multiple definitions. The aim of this paper is to highlight the contribution of various studies dedicated to business failure. An in-depth analysis of the literature as well as the factors explaining distress, leads us to develop a research model of business failure based on a financial approach.